Avaliação dos contatos oclusais em próteses provisórias unitárias implantossuportadas confeccionadas com e sem arco facial - Zamperini, Camila Andrade [UNESP]; Franco, Ana Lúcia [UNESP]; de Faria, Ivan Ribeiro [UNESP] (My University, 2011)
To assess the number of occlusal contacts achieved in temporal prostheses mounted in a semi-adjusted articulator using the facial arch and the Camper plane. Ten patients treated in a private clinic were selected to be rehabilitated with prostheses in previously placed single implants. For each patient two temporal prostheses were designed obtained under different conditions: (1) model mounting using facial arch and (2) Camper plane mounting. Prostheses were made and adjusted in the laboratory and placed only by an operator. The occlusal contacts achieved in each condition were photographed being assessed and quantified by a second professional not involved with the mounting conditions. Results obtained were analyzed by Mann-Whitney test with a 5 % significance level. There was not a statistically difference between the number of occlusal contacts when prostheses were made with facial arch or Camper plane (p= 0.113). The temporal dental prosthesis confection for single implants, semi-adjusted articulator using the Camper plane, not differ very much from the facial arch use, according to the number of resulting occlusal contacts.
Assessment of occlusal contacts in implant-based single temporal prostheses in a semi-adjusted articulator using the facial arch
Keywords: Articulator; Dental occlusion; Facial arch; Implant-based dental prosthesis; Occlusal fitting